2000
DOI: 10.1097/00008571-200006000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The human peroxisome proliferator-activated receptor ?? gene: identification and functional characterization of two natural allelic variants

Abstract: Peroxisome proliferator-activated receptor (PPAR)alpha-null mice have a defect in fatty acid metabolism but reproduce normally. The lack of a detrimental effect of the null phenotype in development and reproduction opens up the possibility for null or variant PPARalpha gene (PPARA) alleles in humans. To search the coding region and splice junctions for mutant and variant PPARalpha alleles, the human PPARalpha gene was cloned and characterized, and sequencing by polymerase chain reaction was carried out. Two po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
1
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 56 publications
4
94
1
4
Order By: Relevance
“…However, the L162V polymorphism has different effects on gene transcription depending on the concentration of ligand. In the presence of high concentrations, transcriptional activity of the G (162V) allele is higher compared with that of the C allele (8,20), whereas at low concentrations results are the opposite (20). In our study and a previous study (10) the presence of the G (162V) allele increased the risk of diabetes.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…However, the L162V polymorphism has different effects on gene transcription depending on the concentration of ligand. In the presence of high concentrations, transcriptional activity of the G (162V) allele is higher compared with that of the C allele (8,20), whereas at low concentrations results are the opposite (20). In our study and a previous study (10) the presence of the G (162V) allele increased the risk of diabetes.…”
Section: Discussionsupporting
confidence: 46%
“…rs1800206 of PPARA is likely to be functional. Transcriptional studies have demonstrated that the C to G change in codon 162 (L162V) of exon 5 encodes a more active PPAR-␣ in vitro (8,20). However, the L162V polymorphism has different effects on gene transcription depending on the concentration of ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The PPARa is a nuclear hormone receptor with a cysteine-rich zinc finger DNA-binding region. Cloning and sequencing of the gene identified two non-synonymous SNPs in the DNA-binding domain (139). Leu162Val which is normally conserved between species, makes the protein unresponsive to low ligand concentrations compared to the wildtype, whilst the mutant allele has also been associated with higher plasma total and low-density lipoprotein (LDL)-apolipoprotein B and LDL-cholesterol in a FrenchCanadian population (140).…”
Section: Ltb 4 Receptors and Pparamentioning
confidence: 99%
“…Several polymorphisms of the human PPAR␣ gene have been described recently (46 -48). Of these, the L162V variant showed decreased non-ligand-dependent transactivation activity and decreased sensitivity to low concentrations of ligand in tissue culture experiments (46). In human studies, it was reported to be associated with elevated plasma low density lipoprotein concentration and increased risk for atherosclerosis and ischemic heart disease (33,47,48).…”
Section: Controlmentioning
confidence: 99%